INTERNATIONAL PUBLIC SECTOR ACCOUNTING STANDARD (IPSAS 24): ITS EFFECT ON PUBLIC SECTOR BUDGET PERFORMANCE IN KWARA STATE, NIGERIA - Salaudeen Ibrahim; Abdul-Hakeem Shuaib; Mubaraq Sanni (Malete Journal of Accounting and Finance)
The reliability of public sector financial information is enhanced through an efficient and transparent financial reporting system. The objective of this study was to investigate the effects of International Public Sector Accounting Standard (IPSAS) compliance on Budget Performance in Nigeria. The targeted population were 50 made up of all 24 members of the Kwara State House of Assembly and 26 Controllers of finance in the state. The sample size for the study was 45 which was arrived at using Kredjcie & Morgan (1970). The survey method of research design was adopted and a well-structured questionnaire designed in four-point Likert-Scale was administered to respondents. The data were analyzed using mean scores and the hypotheses were tested with One Sample T-test. The findings indicated that the level of compliance with disclosures to an extent complied with IPSASs 24 requirements and that IPSAS 24 requirement does have significant impact on budget performance in Kwara State Public Service. The study concluded that the level of compliance with disclosures to an extent complied with IPSAS 24 requirements and therefore recommended that government should continuously train all officers responsible for the implementation of IPSAS and budget implementation so as to update them on the new standards issued by IPSAS Board